Diplomacy and commerce. No 2-5, (1 vol.) (Smith etc., 1840)
No. 2-4. [Reports of public debates between D. Urquhart and others, with other matter]. With tabs. No. 5 Rupture of alliance with France. [By. D. Urquhart]. - With an appendix.